Seawall Construction Impact on Wave Dynamics of Natural Coast (Proceedings of Faculty of Civil Engineering, 2019)
This paper describes the impact of a sea wall on an existing rocky coastline wave dynamic, on the example of the Kostanj beach in Rijeka. Existing and designed significant waves heights were analysed by a numerical wave model Simulating Wave earshore (SWAN), with the application of the original algorithms for illustrating the numerical simulation results. The existing beach design proposes an extension of the existing beach on the western part of the bay by building coastal walls along thenatural coastline. This will increase the wave reflection coefficient relative to the existing coastline. In front of the designed wall a 50-year return period SSE significant wave height will increase from 2,20 to 2,50 m. This paper describes the construction methods for reducing the negative effect of construction of a coastal wall on an existing rocky shoreline. As described and simulated, the submerged breakwater with crown position at 2 m a.s.l. depth, reduces 50 years return period SSE significant wave height from 2,50 to 1,90 m.
Keywords: wave; wave reflection; numerical wave simulation; submerged breakwater